How urban structure can affect city sustainability from an air quality perspective - Borrego, Carlos
Despite the progress made in controlling local air pollution, urban areas show increasing signs of environmental stress and air quality is one of the major concerns. The findings of several studies provide evidence that the shape of a city and the land use distribution determine the location of emission sources and the pattern of urban traffic, affecting urban air quality. This work focuses on the potential impacts of different land use patterns oil urban air quality. Three imaginary cities were created, based on alternative urban planning strategies, considering different land use patterns: from the scenario of urban sprawl to the opposite scenario of a compact city with mixed land use. The mesoscale photochemical system MEMO/MARS was applied to evaluate the urban air quality in each of the idealized city structures. Simulation results indicate that more compact cities with mixed land use provide better urban air quality compared to disperse and network cities.